The rate of progression of type 2 diabetes mellitus to end stage renal disease – A single centred retrospective study from Malaysia. Issue 6 (November 2018) - Ng, Yen Ping; Ahmed, Ramadan; Ooi, Guat See; Lau, Chia Ying; Balasubramanian, Ganesh Pandian; Yap, Cheng Hoon
Highlights: To date Information is still lacking on the rate of progression of T2DM to ESRD in Asian population especially in Malaysia. This study examined the rate of progression of T2DM to ESRD in Malaysian population. This study also investigated the differences in rate of progression of T2DM to ESRD between the patients receiving Renal-Angiotensin-Angiotensinogen-System (RAAS) blocker at time of diagnosis of T2DM and those who did not as well as the costs incurred. Abstract: Introduction: In Malaysia, 61% of dialysis cases are secondary to diabetes. To date, we are still lacking of data on the rate of progression of type 2 diabetes mellitus (T2DM) to end stage renal disease (ESRD) in Malaysia. Materials and methods: This was a retrospective study conducted at nephrology unit of a tertiary hospital in Kedah. All diabetic ESRD patients who fulfilled the inclusion criteria were identified and recruited for analysis. Results: The mean duration of DM to ESRD was found to be 14.37 ± 4.42 years. Mean duration for the onset of diabetic nephropathy was 8.73 ± 3.37 years. There was a relative short duration from diabetic nephropathy to ESRD noted, which was 5.63 ± 2.06 years. The mean duration of DM to ESRD for patients receiving RAAS blocker was found to be 18.23 ± 2.38 years as compared to 11.41 ± 2.94 years for those who did not (95% CI: -0.64 to -2.46). For different type of RAAS blockers, namely ACE inhibitor and angiotensin receptor blocker (ARB), there was no significant difference observed pertaining to mean duration of DM to ESRD; 17.89 ± 1.97 years for ACEi and 19.00 ± 4.16 years for ARB (95% CI: -4.74 to 2.52). Discussion: Time frame from diabetic nephropathy to ESRF among Malaysian population was shorter as compared to findings from other countries with an average period of 15 to 25 years. RAAS blockers should be initiated early in diabetic patients.